2021
DOI: 10.1108/ocj-03-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

A cyber situational awareness model to predict the implementation of cyber security controls and precautions by SMEs

Abstract: PurposeThere is widespread concern about the fact that small- and medium-sized enterprises (SMEs) seem to be particularly vulnerable to cyberattacks. This is perhaps because smaller businesses lack sufficient situational awareness to make informed decisions in this space, or because they lack the resources to implement security controls and precautions.Design/methodology/approachIn this paper, Endsley’s theory of situation awareness was extended to propose a model of SMEs’ cyber situational awareness, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
0
19
1
1
Order By: Relevance
“…Since the first wave of Covid-19, studies highlight that SMEs do not consider themselves favorable targets for cybercrime since they are 'small' [5], [13]. Among the causes of the increased exposure of small businesses are factors ranging from low cybersecurity awareness of personnel, † The Digital Attacks Observatory (OAD) is the only independent online survey in Italy concerned with collecting data regarding digital attacks on IT systems witnessed by companies and public bodies.…”
Section: Cybersecurity: the Context Of Smesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first wave of Covid-19, studies highlight that SMEs do not consider themselves favorable targets for cybercrime since they are 'small' [5], [13]. Among the causes of the increased exposure of small businesses are factors ranging from low cybersecurity awareness of personnel, † The Digital Attacks Observatory (OAD) is the only independent online survey in Italy concerned with collecting data regarding digital attacks on IT systems witnessed by companies and public bodies.…”
Section: Cybersecurity: the Context Of Smesmentioning
confidence: 99%
“…The Allianz Risk Barometer (2022) [4], to which 2,650 risk management experts from 89 countries contributed, reflects this development: cyber incidents have replaced 'business and supply chain interruption' as the top risk. Furthermore, numerous previous studies revealed that SME respondents have reported cyberattacks (e.g., [5]). Consequently, businesses risk millions in damages, reputational losses [6], and business interruptions that jeopardize their continuity and sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small and Medium Businesses (SMBs) are significant to economic development in most countries, especially within the western world, as they represent the majority of businesses (Renaud & Ophoff, 2021;Ward, 2021). Gafni and Pavel (2019) noted that SMBs, a term usually used in the United States (U.S.), while in Europe it is known as Small and Medium Enterprises (SME), may vary in size between countries.…”
Section: Introductionmentioning
confidence: 99%
“…In order to sustain its growth and contribution to the economic growth value-chain system, it is required that MSEs report any cybersecurity incidents that occur in their business operations to the CSIRT or SOC in their sector. However, many MSEs are seen to have a very weak defence against cyber-attacks and lack the importance of cybersecurity; thus, they do not have good knowledge of the precautions to adopt in the face of cyber incidents [8][9][10][11]. For cybersecurity incidents to be reported, stakeholders of MSEs need to know the medium of reporting, and the organisations they should report attacks to.…”
Section: Introductionmentioning
confidence: 99%